Advances in carrier-bound and carrier-free immobilized nanobiocatalysts. (2nd October 2015) - Wang, Mengfan; Qi, Wei; Su, Rongxin; He, Zhimin
Abstract: Although the immobilization of enzymes with improved activity and stability has been the subject of growing interest for many years, new opportunities arose by implementing nanomaterials as immobilizing carriers. The nano-carriers not only offer larger surface area and lower mass-transfer limitation but also endow the native enzyme with specific performances due to their various physical or chemical properties. A carrier-free nanobiocatalyst, cross-linked enzyme aggregates (CLEAs), has been developed for applications in industrial bioprocesses. This review illustrates the recent achievements in nanobiocatalysts, including the carrier-bound and carrier-free enzymes. These nanobiocatalysts provide enzymes with broad properties to serve in the fields of biocatalysis, biomedicine and biosensors. Highlights: Nanobiocatalysts have been developed as an attractive strategy for enzyme immobilization in biocatalysis and biosensor fields. The carrier-bound nanobiocatalysts exhibit specific performances by combining enzymes with nanomaterials. Cross-linked enzyme aggregates shows higher activity and stability than native enzymes as carrier-free nanobiocatalysts.